Kiai’s Situational and Transformative Leadership: Maintaining The Quality of Pesantren Graduates in The Disruption Era - Elis Nursetialloh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The enduring presence of Islamic boarding schools (pesantren) as vital Islamic educational institutions across dynamic epochs is a testament to their adaptability. This study unravels the strategies employed by pesantren to maintain the quality of their graduates in the face of contemporary challenges. Specifically, it investigates the role of Kiai leadership styles (situational and transformative) in fostering robust graduates, alongside exploring how pesantren educational management adapts to the age of disruption driven by technological advancements. Employing a multi-site approach, the study examines two pesantrens in Central Java that have modernized their educational systems to navigate the disruptive era. Data collection involves in-depth interviews, observations, and document analysis. Following Milles and Hubberman's framework, data undergoes reduction, display, verification, and subsequent conclusion drawing. The findings disclose significant similarities in Kiai leadership styles between Pondok Pesantren Al-Istiqomah Batang and Pondok Pesantren Walindo Pekalongan. Both Kiais exhibit adeptness in reading situational dynamics and choosing effective leadership approaches, a crucial quality in a disruptive era. The study also identifies nuanced differences in their educational management systems. Pondok Pesantren Walindo integrates formal education with madrasah diniyah (Islamic religious education), whereas Pondok Pesantren Al-Istiqomah maintains a separate system. These variations present distinct strengths and weaknesses, impacting each pesantren's capacity to nurture high-caliber graduates. This research contributes to understanding the dynamic landscapes of pesantren education in the face of disruption, highlighting the role of adaptable leadership and educational management in ensuring robust academic outcomes.